De/signing research in education: patchwork(ing) methodologies with theory. Issue 1 (1st January 2017) - Higgins, Marc; Madden, Brooke; Berard, Marie-France; Lenz Kothe, Elsa; Nordstrom, Susan
Abstract: Four education scholars extend the methodological space inspired by Jackson and Mazzei's Thinking with Theory through focusing on research design. The notion of de/sign is presented and employed to counter prescriptive method/ology that often sutures over pedagogical possibilities in research and educational settings. Key methodological themes (e.g. voice, agency, subjectivity, data) are (un)tailored in order to work within, against, and beyond conventional humanist qualitative methodology. Patchwork methodologies take shape as key theorists and theories pierce, (un)stitch, snag, embroider, patch, and mend the fabrics of distinct research contexts, components, and commitments. Previews of the productions that result from attending to the enacted and embodied relationship between theory and research de/sign are presented. A discussion of the ways in which patchwork(ing) methodologies provokes new questions, analytical frames, and types of findings concludes the article.